Increase in pituitary adenosine 3′:5′-cyclic monophosphate content and potentiation of growth-hormone release from heifer anterior pituitary slices incubated in the presence of 3-isobutyl-1-methylxanthine - Schofield, J. George (1974)
The release of growth hormone from heifer anterior pituitary slices and the cyclic AMP content of the slices were increased by the phosphodiesterase inhibitor 3-isobutyl-1-methylxanthine, both increases being related to inhibitor concentration over the range 0.1–1.0mm. Neither Ba(2+) (6.9 or 2.3mm), K(+) (72mm), nor p-chloromercuribenzoate (20μm) had any effect on pituitary cyclic AMP content over a 20min period. 3-Isobutyl-1-methylxanthine potentiated the release of growth hormone in response to Ba(2+) (2.3mm) and K(+) (24mm), but the degree of potentiation did not depend on inhibitor concentration in the same way as did tissue cyclic AMP content. 3-Isobutyl-1-methylxanthine decreased the concentration of K(+) required to give maximum stimulation of growth-hormone release, but did not significantly increase the maximum response to Ba(2+). Growth-hormone release in the presence of prostaglandin E(2) (1μm) was increased by 3-isobutyl-1-methylxanthine and was inhibited by the prostaglandin antagonist, 7-oxa-13-prostynoic acid, although this antagonist increased the pituitary cyclic AMP concentration and potentiated the prostaglandin E(2)-induced rise in cyclic AMP content. The stimulation of growth-hormone release by p-chloromercuribenzoate was not potentiated by 3-isobutyl-1-methylxanthine. The data suggest that Ba(+) and K(+) act at the same point in the secretory process as 3-isobutyl-1-methylxanthine, although by a different mechanism, and that p-chloromercuribenzoate has a different point of action.